Covid-19 as a catalyst for sustainable change: the rise of democratic pedagogical partnership in initial teacher education in Ireland. Issue 2 (3rd April 2021) - Farrell, Rachel
Abstract : While challenges faced by school leaders during the COVID-19 pandemic have been extensively discussed, this article explores ways in which student teachers have demonstrated 'adaptive expertise' in response to a changing educational landscape that have enabled them to support schools during this public health emergency. Discerning school leaders have over the past twelve months looked to student teachers on school placement to demonstrate teacher leadership in supporting schools during the COVID-19 education crisis. This qualitative research draws on in-depth interviews with school leaders [10], co-operating teachers [10] and student teachers [10] across ten case study schools on a teacher education programme in Ireland. It highlights the way in which the COVID-19 pandemic has provided an impetus for the development of democratic pedagogical partnerships in ITE triggered by a need for collaborative engagement underpinned by responsive pedagogy and digital enhanced learning. The data also supports the view that the expertise that student teachers can offer schools in relation to their digital competence can significantly assist in fostering collaborative and reflective practice and bridge the perennial theory/practice divide.